Evaluation of a one‐hour asynchronous video training for eating disorder screening and referral in U.S. Pediatric Primary Care: A pilot study. Issue 9 (4th July 2022) - Raffoul, Amanda; Vitagliano, Julia A.; Sarda, Vishnudas; Chan, Charmaine; Chwa, Cindy; Ferreira, Katelyn B.; Gooding, Holly C.; Forman, Sara F.; Austin, S. Bryn
Abstract: Objective: Develop and pilot‐test the efficacy of an online training in improving comfort, knowledge, and behaviors related to eating disorders (EDs) screening among U.S.‐based pediatric primary care providers (PCPs). Methods: PCPs ( N  = 84) completed a baseline survey assessing comfort, knowledge, and behaviors regarding ED screening and referral, then watched a 1‐h training video followed by a post‐video survey. Half of the participants were randomly assigned to complete spaced‐education questions in the following 2 months. All participants completed a 2‐month follow‐up survey. We used McNemar's and McNemar–Bowker tests to assess differences from baseline to post‐video and post‐video to follow‐up, and logistic models to assess differences by spaced‐education condition. Results: From baseline to post‐video, there were significant improvements in PCPs' knowledge about and comfort in screening and making referrals for EDs ( p  < .05). There were no differences between spaced‐education conditions in knowledge and behaviors from baseline or post‐video to follow‐up, but spaced‐education participants reported significantly greater comfort in screening for BN ( p  < .01) and BED ( p  < .01) compared to non‐spaced‐education participants. Discussion: Findings suggest that a 1‐h asynchronous training can improve PCP comfort, knowledge, and behavior in screening for EDs; spaced‐education may provide slight additional benefits in PCP comfort. Public Significance: The delivery of an 1‐h asynchronous online video training helped to improve PCPs' comfort, knowledge, and behavior in screening and referral for EDs among pediatric populations. This has implications for future evaluations of brief trainings among this provider population, which could ultimately help to improve early identification of EDs and referrals to appropriate treatment.